If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = -4x Reorder the terms: -4 + 2x = -4x Solving -4 + 2x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -4 + 2x + 4x = -4x + 4x Combine like terms: 2x + 4x = 6x -4 + 6x = -4x + 4x Combine like terms: -4x + 4x = 0 -4 + 6x = 0 Add '4' to each side of the equation. -4 + 4 + 6x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 0 + 4 6x = 0 + 4 Combine like terms: 0 + 4 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 4m-(-2)=18 | | 9p^2=24p-16 | | 3x-5(5x+17)=69 | | 8*15/6 | | 1/7*6/7 | | 4-(-2)=18 | | 2x+5x-6=15 | | 21x-5=5(4x+2)-5 | | -4x+6(-2x-2)=84 | | 2r^2-3=-3-2(2r-r^2) | | 1/4t+1=9/4 | | 500+0.35x=2.5x | | 3x-7+x^2+3x-4=11 | | 2(2y+8)-y=16 | | 10(v+2)-2v=2(4v+3)-11 | | 7/9*21/2 | | 1/4t+1=21/4 | | 2/3*1/7 | | -8x-(4x+6)=14 | | ax+ry=n | | 4x=-27 | | -6x-4(x-12)=158 | | 3x^2+-8x+4=0 | | 3/5x=-7/8 | | x^4-28x^2+100=0 | | -3(3-2r)=6r+21 | | (1/4)(3t-7)=(t+7)/8 | | -8-8/3 | | 4x^2-7x+11x=2x+6 | | -8-16/8 | | .4x-.2=.3x+3 | | x^2+22x+23=0 |